Hubungan IMT, Persentase Lemak, Lingkar Pinggang terhadap Status Gejala Menopause pada Peri-Menopause di Pengajian Kelurahan Semper - Yulianti, Monica; Franciska, Shelly; Sutanto, Luciana Budi; Winaktu, Gracia JMT (Jurnal MedScientiae, 2025)
Nutritional status, such as Body Mass Index (BMI), body fat percentage, and waist circumference, are important indicators related to body composition. Increased body fat can trigger hormonal imbalances that affect the severity of menopausal symptoms. The aim of this study was to analyze the relationship between nutritional status and the severity of menopausal symptoms among 135 respondents selected purposively in May 2025. This study employed an observational cross-sectional design and statistical analysis using the chi-square test (p < 0.05). The results showed that the majority of respondents were classified as obese based on body fat percentage (77%) and waist circumference (81.5%). Menopausal symptoms were generally in the moderate category (40%), mild (20.7%), and severe (11.9%). There was a significant association between excessive nutritional status and the severity of menopausal symptoms. In conclusion, excessive nutritional status is associated with increased severity of menopausal symptoms.